Key stage 3 geographical enquiry - Weatherly, David; Sheehan, Nicholas; Kitchen, Rebecca (Collins, 2015)
Case studies in the book will include: samples of the breadth studies at Key Stage 3, key processes in both physical and human geography, integration of higher order thinking skills to exemplify that the world is a complex and interconnected place. Enquiry topics: 1. Frozen landscapes - Do corries really prefer north facing slopes? -- 2. On thin ice - Can Russia exploit the Arctic sustainably? -- 3. Welcome to Quake City, New Zealand - How has Christchurch been affected by earthquakes? -- 4. Managing the coast - When is doing nothing actually doing something? -- 5. Life's a beach - Why do most Australians live on the edge? -- 6. Preventing history repeating itself - What is being done to save Allerford? -- 7. The world's other population problem - What should the European Union do about its declining population?